Turán Type Inequalities For the (p,k)-Generalization of the Mittag-Leffler Function - ÇETİNKAYA, ASENA; Altınkaya, Şahsene; Mert, Oya (Springer, 2024)
The Turán type inequalities attract attention in a variety of research fields such as orthogonal polynomials and special functions. Using the newly established (p, k)-generalization of the Mittag-Leffler function, we derive new Turán type inequalities. These outcomes are the generalization of several findings in the literature. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
Operators, Inequalities and Approximation
Keywords: p. k)-Gamma Function; (p. k)-Mittag-Leffler Function; (p. k)-Pochhammer Symbol; Legendre Polynomial; Turán Type Inequalities